2019
DOI: 10.1177/1078155219845432
|View full text |Cite
|
Sign up to set email alerts
|

Work overload is related to increased risk of error during chemotherapy preparation

Abstract: Purpose Chemotherapy preparation units face peaks in activity leading to high workloads and increased stress. The present study evaluated the impact of work overloads on the safety and accuracy of manual preparations. Method Simulating overwork, operators were asked to produce increasing numbers of syringes (8, 16, and 24), with markers (phenylephrine or lidocaine), within 1 h, in an isolator, under aseptic conditions. Results were analyzed using qualitative and quantitative criteria. Concentration deviations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…18 They found that it was clear that a large number of vials and a large volume of active solution, respectively related to low dosing and low concentration, induced a multiplication of manipulations, and increased the Several publications consider the link between workload and error at work, in medical sectors as in other sectors, such as aviation or car manufacturing chains, but none explore the relationship between day-to-day workload. [17][18][19] This also raises the question of maintaining quality when the workload exceeds the team's production capacity, including days when the workload is low.…”
Section: Discussionmentioning
confidence: 99%
“…18 They found that it was clear that a large number of vials and a large volume of active solution, respectively related to low dosing and low concentration, induced a multiplication of manipulations, and increased the Several publications consider the link between workload and error at work, in medical sectors as in other sectors, such as aviation or car manufacturing chains, but none explore the relationship between day-to-day workload. [17][18][19] This also raises the question of maintaining quality when the workload exceeds the team's production capacity, including days when the workload is low.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of new technology in the workplace requires effortful reconsideration and relearning process, which can introduce additional workload to staff in a high-stress and high-demands work environment. Work overload and fatigue can result in errors (Carrez et al, 2019;Dimova et al, 2018), which can increase the clinical burden and compromise the quality of patient care (Chase et al, 2008). Since patient care is core to healthcare staff's professional pride and identity, medical decision-makers must invest in resources to support the implementation of any new technology as a precaution to preventing negative attitudes about the technology from forming.…”
Section: Workload Managementmentioning
confidence: 99%
“…This same study found that pharmacy staff more frequently attributed errors they made to a high workload. More recently a Swiss study evaluated the impact of simulated workloads on accuracy and error rates in manual aseptic preparations 1. Three 1 hour scenarios were designed to replicate low, medium and high workloads.…”
Section: Introductionmentioning
confidence: 99%